2006
DOI: 10.1007/s00330-006-0488-7
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler, power Doppler and B-flow ultrasound in the assessment of ICA stenosis: Comparison with 64-MD-CT angiography

Abstract: The purpose of this study is to investigate the diagnostic potential of color-coded Doppler sonography (CCDS), power-Doppler (PD) and B-flow ultrasound in assessing the degree of extracranial internal carotid artery (ICA) stenosis in comparison to CT-angiography (MD-CTA). Thirty-two consecutive patients referred for CTA with 41 ICA-stenoses were included in this prospective study. MD-CTA was performed using a 64 row scanner with a CTDIvol of 13.1 mGy/cm. In CTA, CCDS, PD and B-flow, the degree of stenosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 45 publications
0
34
0
4
Order By: Relevance
“…Rapid image acquisition and processing, continuous image acquisition ("spiral CT"), and multiple-detector systems have made highresolution CTA clinically practical. [193][194][195][196][197][198][199] Like MRA, CTA provides anatomic imaging from the aortic arch through the circle of Willis. Multiplanar reconstruction and analysis allows evaluation of even very tortuous vessels.…”
Section: Computed Tomographic Angiographymentioning
confidence: 99%
“…Rapid image acquisition and processing, continuous image acquisition ("spiral CT"), and multiple-detector systems have made highresolution CTA clinically practical. [193][194][195][196][197][198][199] Like MRA, CTA provides anatomic imaging from the aortic arch through the circle of Willis. Multiplanar reconstruction and analysis allows evaluation of even very tortuous vessels.…”
Section: Computed Tomographic Angiographymentioning
confidence: 99%
“…Clevert et al reported that Bflow, which is quite similar technology to the EFI utilized in the present study, provided better ultrasonographic diagnosis of ICA stenosis as compared with color Doppler flow imaging and power Doppler imaging as a result of negligible pulsation and blooming artifacts. 26 Some studies have demonstrated a good correlation between the NASCET measurement by B-flow and by DSA. 27,28 Similar to B-flow, EFI is able to visualize blood flow with improved spatial and temporal resolution by applying a composite pulse emission technique.…”
Section: Discussionmentioning
confidence: 95%
“…However, catheter-based DSA bears the risk of complications due to its invasiveness, specifically the risk of stroke. Noninvasive diagnostic alternatives include duplex ultrasonography, CTA and MRA [5,19]. ANOVA (analysis of variance) of the three image quality parameters with the two independent factors "image registration method" and "body shift class" revealed no statistically significant results at p<0.05, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…A comparison of registration methods is given in Fig. 1 VDP vessel detection probability, CNR-MIP contrast-to-noise ratio in MIP images, CNR-3D contrast-to-noise ratio in 3D subtraction image volumes a All F ratios (variance ratios) are based on the residual mean square error Duplex ultrasonography is being used as a screening method, whereas CTA and MRA provide images of the entire cervical arterial tree that may be referred to during surgical or neuroendovascular intervention [7,19,20]. For the detection of severe 70-99% carotid artery stenosis according to the NASCETcriteria, a recent meta-analysis found contrastenhanced MRA to be more sensitive and specific than CTA or duplex ultrasonography (respective sensitivities of 94%, 76% and 89% with specificities of 93%, 94% and 84%) [7].…”
Section: Discussionmentioning
confidence: 99%